Réponses

2013-12-16T17:13:51+01:00
Bonjour,

1)\ (\dfrac{e^x}{x})'=\dfrac{(e^x)'\times x-x'\times e^x}{x^2}\\\\(\dfrac{e^x}{x})'=\dfrac{e^x\times x-1\times e^x}{x^2}\\\\(\dfrac{e^x}{x})'=\dfrac{xe^x-e^x}{x^2}\\\\(\dfrac{e^x}{x})'=\dfrac{(x-1)e^x}{x^2}

2)\ (\dfrac{x}{e^x})'=\dfrac{x'\times e^x-(e^x)'\times x}{(e^x)^2}\\\\(\dfrac{x}{e^x})'=\dfrac{1\times e^x-e^x\times x}{(e^x)^2}\\\\(\dfrac{x}{e^x})'=\dfrac{(1-x)e^x }{(e^x)^2}\\\\(\dfrac{x}{e^x})'=\dfrac{1-x }{e^x}

ou encore 

2)\ (\dfrac{x}{e^x})'=(e^{-x}\times x)'=(e^{-x})'\times x+x'\times e^{-x}\\\\=-e^{-x}\times x+1\times e^{-x}\\\\=-xe^{-x}+e^{-x}\\\\=e^{-x}(-x+1)

Les deux réponses sont équivalentes.